PRODUCT DEVELOPMENT WITHIN THE SCOPE OF CIRCULAR ECONOMY FROM FUNCTIONAL FOOD WASTES GENERATED IN THE PRODUCTION PROCESS IN AGRICULTURAL DEVELOPMENT COOPERATIVE: THE CASE OF DEVREK CRANBERRY SORBET AND DEVREK CRANBERRY ICE CREAM (Third Sector Social Economic Review, 2025)
In the search for solutions to global environmental problems, circular economy plays an important role in the utilization of food waste. In this study, from the perspective of circular economy, it is aimed to utilize the wastes of Devrek cranberry fruit, a geographical sign registered functional food of Zonguldak province and transform them into new products. Especially by developing products such as ice cream and sorbet, it is aimed both to reduce food waste and to utilize the functional properties of kiren fruit in different products. Another important aim of the study is to determine the level of acceptance of these new products by consumers and to examine the impact of circular economic practices on consumer behavior. The application part of the study was carried out in partnership with Zonguldak Bülent Ecevit University Devrek Vocational School Culinary Practice and Training Kitchen and Devrek Güneşi Women's Cooperative Production Workshop. While the processing of Devrek cranberry fruits and obtaining cranberry sour and pulp were carried out by the cooperative members, the evaluation of cranberry pulp in ice cream and sorbet production was carried out by the researchers. In this way, both academic knowledge and skills and the experiences of local producers were brought together and a comprehensive study on the utilization of Devrek cranberry fruit waste was carried out. As a result of the experiments, 5 different ice cream and 2 sorbet varieties were obtained from cranberry fruit, which is a functional food, Devrek cranberry pulp and cranberry sour obtained from the processing of cranberry fruit. The sensory properties and consumer acceptance of cranberry ice cream and cranberry sorbet products developed within the scope of the study were investigated by experimental design, which is one of the quantitative research methods. Identification was used as one of the analysis techniques and profile analysis was used for evaluation. According to the results of the sensory evaluation carried out within the scope of the study, the findings obtained revealed that the different ingredients and ratios used in the development process of cranberry ice cream recipe significantly affected the sensory properties. Cranberry ice cream obtained from Devrek cranberry fruit was the most favorite product in terms of all sensory characteristics and general consumer liking. The products developed with the closest sensory characteristics and general appreciation rate to cranberry ice cream obtained from Devrek cranberry fruit were kiren ice cream obtained from cranberry pulp and cranberry ice cream obtained from a mixture of Devrek cranberry fruit and pulp. Obtaining this result was an important result in achieving the aim of the study in terms of using cranberry pulp in ice cream production, preventing food waste and efficient use of resources.
Keywords: Agricultural Development Cooperative; Gastronomy; Cranberry; Functional Food; Ice Cream; Circular Economy; Food Waste.